Magnesium-based sacrificial anode material protection biological membrane and preparation method and protection method thereof

By forming a Bacillus altitudedinis biofilm on the surface of the magnesium-based sacrificial anode material, the problem of high self-corrosion rate of magnesium alloy in water environment is solved, and efficient anode protection is achieved.

CN119824425APending Publication Date: 2025-04-15SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510042228.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

As a sacrificial anode material, the high self-corrosion rate of magnesium alloys limits their application in water environment systems.

Method used

The self-corrosion of magnesium is inhibited by immersing the magnesium-based sacrificial anode material in Bacillus altitudinis bacterial solution to form a biofilm. When the cathode material needs protection, the current inactivates the biofilm and activates the protection of the magnesium anode.

Benefits of technology

It effectively inhibits the self-corrosion of magnesium, improves the anode protection efficiency, which is significantly higher than the protection efficiency of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824425A_ABST
    Figure CN119824425A_ABST
Patent Text Reader

Abstract

The invention discloses a magnesium-based sacrificial anode material protection biological membrane and a preparation method and a protection method thereof, and the preparation method comprises the following steps: immersing a magnesium-based sacrificial anode material in a Bacillus altitudinis bacterial solution, culturing for a set time, and forming a biological membrane on the surface of the magnesium-based sacrificial anode material to obtain the magnesium-based sacrificial anode material protection biological membrane. And when the cathode material needs to be protected, the current of the magnesium steel enables the bacterial biofilm to be inactivated, and the magnesium anode is triggered to start protection, so that an intelligent biofilm protection system is constructed for the magnesium anode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium-based sacrificial anode materials, and in particular relates to a magnesium-based sacrificial anode material protective biofilm and a preparation method thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] With the rapid development of water conservancy projects, the damage and failure of engineering materials have hindered the development and utilization of water resources. Among them, the corrosion of steel seriously affects the safety, reliability and integrity of water conservancy facilities. At present, the main methods for inhibiting steel corrosion are physical methods, chemical methods and electrochemical methods. The cathodic protection method of sacrificial anode is one of the effective technologies for controlling steel corrosion. Magnesium (Mg), aluminum (Al), zinc (Zn) and their alloys are currently the main sacrificial anode materials. Among them, magnesium and its alloys can be used as ideal sacrificial anodes because of their advantages such as large power generation per unit mass and appropriate driving potential for the protected metal. However, due to the high self-corrosion rate of magnesium alloys, their application in freshwater environments and even desalinated seawater systems around coastal cities is severely restricted.

[0004] To solve this problem, the preparation technology of new alloys has been widely developed. However, the alloying process is relatively complicated and cumbersome. If a simpler and more convenient method can be developed to enable magnesium anodes to be used in water environments with high anode efficiency, this will greatly broaden the application range of magnesium and its alloys. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a magnesium-based sacrificial anode material protective biofilm and a preparation method thereof.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a magnesium-based sacrificial anode material protective biofilm, comprising the following steps:

[0008] The magnesium-based sacrificial anode material is immersed in a Bacillus altitudinis bacterial solution and cultured for a set time to form a biofilm on the surface of the magnesium-based sacrificial anode material.

[0009] The bacteria Bacillus altitudinis can survive under highly alkaline conditions and form biofilms attached to magnesium surfaces. The biofilm of B.altitudinis can inhibit magnesium corrosion by an order of magnitude. This is due to the deposition of a layer of crystalline MgNH4PO4·6H2O, the formation of a bacterial biofilm dominated by EPS, and the upregulation of metabolites in the biofilm. The release of moderate concentrations of magnesium ions effectively activates bacterial cells, forming a mutually beneficial system consisting of active bacterial biofilms and magnesium matrices. Inspired by this, when the cathode material does not need protection, highly active biofilms can be used to inhibit the self-corrosion of the magnesium anode. When the cathode material needs protection, the current of the magnesium steel inactivates the bacterial biofilm, triggering the magnesium anode to start protection, thereby building an intelligent biofilm protection system for the magnesium anode.

[0010] In some embodiments, the concentration of the Bacillus altitudinis bacterial solution is 10 4 -10 6 CFU / mL;

[0011] Preferably, the concentration of the Bacillus altitudinis bacterial solution is 10 5 CFU / mL.

[0012] In some embodiments, the magnesium-based sacrificial anode material is pure magnesium, Mg-6Al-3Zn (AZ63), Mg-5Al-0.5Zn (AZ505A), AZ91D, Mg-0.5Mn (MM05), Mg-6Al-3Zn-0.2Mn (GALFAN), Mg-5Al-0.5Zn-0.5Mn-0.5RE (GR50), Mg-6Al-3Zn-0.5RE (E-SAC) or Mg-7Al-1Zn-0.2Ca-0.2Sr (HEC-MAG).

[0013] In some embodiments, the magnesium-based sacrificial anode material is cultured in a Bacillus altitudinis bacterial solution for 5-10 days, preferably 6-8 days, and more preferably 7 days.

[0014] In some embodiments, the temperature at which the magnesium-based sacrificial anode material is cultured in the Bacillus altitudinis bacterial solution is 28-37°C.

[0015] In some embodiments, the pH value of the Bacillus altitudinis bacterial solution is 7-9, and the magnesium anode material is polished with 400-1200 mesh sandpaper, and then the immersion experiment is started after cleaning and sterilization.

[0016] In a second aspect, the present invention provides a magnesium-based sacrificial anode material protective biofilm, which is prepared by the preparation method.

[0017] In a third aspect, the present invention provides a method for protecting a magnesium-based sacrificial anode material by using the magnesium-based sacrificial anode material protection biofilm, comprising the following steps:

[0018] When the cathode material does not need protection, there is no current between the cathode material and the magnesium-based sacrificial anode material. At this time, the biofilm on the surface of the magnesium-based sacrificial anode material protects the magnesium-based sacrificial anode material and inhibits its self-corrosion.

[0019] When the cathode material needs protection, the current formed between the cathode material and the magnesium-based sacrificial anode material inactivates the biofilm, and the protection of the cathode material by the magnesium-based sacrificial anode material is initiated.

[0020] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0021] Magnesium alloy is an excellent sacrificial anode material, but its high self-corrosion rate limits its application in water environment systems. The present invention develops a method for protecting magnesium alloy sacrificial anode materials with bacterial biofilm, and tests the potential difference of -1.5V, -1.4V, -1.3V and -1.2V and the galvanic system of Mg-Q235 carbon steel. The magnesium sample is immersed in a bacterial concentration of 10 5 CFU / mL of Bacillus altitudinis was cultured for 7 days, and a biofilm with a mean fluorescence efficiency (MFI) of 78.5±10.9% was formed on the 7th day. The biofilm effectively inhibited the self-corrosion of magnesium and reduced its corrosion rate to a minimum of 11.53±0.06μA cm -2 . When the cathode material needs to be protected, the galvanic current will inactivate the biofilm, and the magnesium anode can provide the protective current normally. The study found that at -1.3V, -1.4V and when Q235 carbon steel was coupled with magnesium, the anode protection efficiency reached 70.9±2.8%, 73.3±1.8% and 79.8±0.9%, respectively, which is significantly higher than the protection efficiency of about 50% widely reported in the literature.

[0022] The present invention realizes the protection of anode materials and the improvement of anode efficiency through intelligent biofilm. 5 CFU mL -1 The highly active biofilm cultured for 7 days at a bacterial concentration of 1.57 μg / cm2 provided sufficient protection for the anode material. The impedance value of magnesium in the biological culture medium (9082±168.7Ωcm 2 ) than the impedance value in sterile culture medium (1320±215.6Ωcm 2) is nearly an order of magnitude higher. When anodic protection is needed, the current of Mg-Fe kills the bacterial biofilm and activates the cathodic protection of Q235CS. Ultimately, the protection efficiency of the magnesium anode coupled with Q235 CS is increased to 79.8±0.9%. At the same time, the magnesium anode still maintains good performance after use, with an impedance value of up to 1174±23.3Ωcm 2 In addition, the biofilm can also improve the anode efficiency to 73.34±1.8% and 70.92±2.8% when the potential difference between the metal and magnesium is 1.3V and 1.4V, respectively. Looking forward to the future, the biofilm protection technology will be applied to more cathode metal materials, not just limited to Q235 carbon steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0024] Figure 1 (a) shows the absorbance and the relationship between planktonic B.altitudinis (N B.altitudinis ) The corresponding relationship between the number of ; (b) is the growth curve of B.altitudinis; (c) is the change of pH value with time in the presence or absence of B.altitudinis;

[0025] Figure 2 In the figure, (a) shows the polarization curves of Mg and Q235 CS in biological culture medium; (b) summarizes the E calculated based on the polarization curves in a. gi s and i gi s;

[0026] Figure 3 In the Mg sample, the 5 CFU mL -1 SEM images of biofilm morphology after immersion in bacterial culture medium for (a) 3 days, (b) 4 days, (c) 5 days, (e) 6 days, and (g) 7 days; high-magnification images of biofilm after immersion in bacterial culture medium for (d) 5 days, (f) 6 days, and (h) 7 days;

[0027] Figure 4 In the Mg sample, the 5 CFU mL -1 CLSM images after culture in bacterial culture medium for (a) 3 days, (b) 4 days, (c) 5 days, (d) 6 days, and (e) 7 days, and (f) mean fluorescence intensity (MFI) distribution;

[0028] Figure 5 For Mg and Q235 CS, respectively, 5 CFU mL -1(a) OCP after immersion in bacterial culture medium and sterile culture medium for 7 days; (b) polarization curve;

[0029] Figure 6 For Mg and Q235 CS samples at 10 5 CFU mL -1 EIS spectra after immersion in bacterial culture medium for 7 days; wherein, (a) is the equivalent circuit fitting the EIS of magnesium sample in bacterial culture medium; (b) is the equivalent circuit fitting the EIS of magnesium sample in sterile culture medium; (c) is the EIS spectrum of Mg sample in bacterial culture medium; (d) is the EIS spectrum of Mg sample in sterile culture medium; (e) is the EIS spectrum of Q235 CS sample in bacterial culture medium; (f) is the EIS spectrum of Q235 CS sample in sterile culture medium;

[0030] Figure 7 The Mg samples were sterile and 10 5 CFU mL -1 Is and I at different potentials in bacterial culture medium after constant potential test at -1.5V (a and a'), -1.4V (c and c'), -1.3V (d and d'), -1.2V (e and e') and Mg-Fe couple test (b and b') g ;

[0031] Figure 8 (a) Mg after constant potential corrosion and galvanic corrosion tests 2+ Dissolution concentration of Mg samples in sterile and 10 5 CFU mL -1 Anode efficiency after 7200 s of constant potential and galvanic corrosion testing in bacterial culture medium;

[0032] Fig. 9 In the Mg sample, the 5 CFU mL -1 CLSM images after constant potential tests at (a) -1.5V, (b) -1.4V, (c) -1.3V, and (d) -1.2V in bacterial culture medium; (e) CLSM image after Mg-Fe galvanic corrosion test; (f) mean fluorescence intensity (MFI) distribution;

[0033] Fig.10 Equivalent circuits for fitting EIS spectra of (a) bacteria-containing and (b) sterile samples; EIS spectra of Mg anode (a and b) and Q235CS (c and d) in sterile and 10 5 CFU mL -1 EIS spectra after constant potential tests and galvanic corrosion tests at different potentials in bacterial culture medium.

[0034] Fig.11The membrane resistance values ​​(R) of Mg (a and c) and Q235 CS (b and d) after 7 days of incubation and constant potential and galvanic corrosion tests f ) and electron transfer resistance (R ct );

[0035] Fig.12 In the case of Mg, 10 5 CFU mL -1 The deepest pitting morphology of bacteria-containing (a and b) and sterile (c and d) culture media after 7200s of constant potential test at -1.5V; (e) 10 5 CFU mL -1 Comparison of maximum and average pitting depths in sterile and aseptic media; (f) Pitting depth distribution;

[0036] Fig.13 In the case of Mg, 10 5 CFU mL -1 The deepest pitting morphology of bacteria-containing (a and b) and sterile (c and d) culture media after 7200s of Mg-Fe galvanic corrosion test; (e) 10 5 CFU mL -1 Comparison of maximum and average pitting depths in sterile and aseptic media; (f) Pitting depth distribution;

[0037] Fig.14 In the case of Mg, 10 5 CFU mL -1 The deepest pitting morphology of bacteria-containing (a and b) and sterile (c and d) culture media after 7200s of constant potential test at -1.4V;

[0038] Fig.15 In the case of Mg, 10 5 CFU mL -1 The deepest pitting morphology of bacteria-containing (a and b) and sterile (c and d) culture media after constant potential testing at -1.3 V for 7200 s;

[0039] Fig.16 In the case of Mg, 10 5 CFU mL -1 The deepest pitting morphologies of bacteria-containing (a and b) and sterile (c and d) culture media after constant potential testing at -1.2 V for 7200 s. DETAILED DESCRIPTION

[0040] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0041] The present invention will be further described below in conjunction with the embodiments.

[0042] Material

[0043] Pure magnesium was used as the sacrificial anode material in this work and was purchased from Hebei Zhonghui Metal Materials Co., Ltd.

[0044] The chemical composition (mass fraction) of pure magnesium is: 0.01% Al, 0.001% Zn, 0.01% Mn, 0.002% Cu, 0.001% Ni, 0.003% Fe, 0.003% Cl, and the rest is Mg.

[0045] Q235 carbon steel (CS) was selected as the cathode material in the galvanic corrosion test and was purchased from Jiangsu Jinli Precision Machinery Co., Ltd.

[0046] The chemical composition (mass fraction) of Q235 CS is: 0.18% C, 0.17% S, 0.45% Mn, 0.026% P, 0.016% S, and the rest is Fe.

[0047] All samples were cut into sizes of 10×10×10 mm.

[0048] After the copper wires are connected to the back side, they are fixed with epoxy, leaving only a 1 cm2 working surface exposed.

[0049] Before testing, the samples were polished with 400-mesh, 600-mesh, 800-mesh, 1000-mesh, and 1200-mesh sandpapers in turn, then rinsed with anhydrous ethanol and sterilized under ultraviolet light for 30 minutes.

[0050] Microbial culture

[0051] The strain used in this study was derived from the symbiotic algae inoculum (Phaeodactylum tricornutum) purchased from the Marine Biological Resources Center, Institute of Oceanology, Chinese Academy of Sciences (Qingdao), and was identified as Bacillus altitudinis by 16S rDNA sequence analysis (see Biocorrosion induced by red-tide alga-bacterium symbiosis and the biofouling induced by dissolved iron for carbon steel inmarine environment, Yuqiao Dong et al., Journal of Materials Science & Technology 128 (2022) 107-117). The strain was inoculated in LB medium for activation culture at a concentration of 10 5CFU / mL of bacteria were used as the experimental group, and sterile culture medium was used as the control group.

[0052] The absorbance of the bacterial solution at a wavelength of 600 nm (OD 600) was measured using an ultraviolet spectrophotometer (UV-1800, Shimadzu, Japan) to establish a standard curve between the number of bacteria and the OD value and the growth curve of B. altitudinis.

[0053] The specific method is as follows: first, a standard curve of bacterial count and OD value is established. After the bacteria cultured to the logarithmic growth phase are diluted at different times, the absorbance of the bacterial solution at each dilution multiple is detected by a UV spectrophotometer, and then the number of bacteria at the corresponding concentration is calculated using a flow cytometer (BD Accuri C6 Plus, Becton Dickinson, USA). The bacteria are inoculated into sterile culture medium, 2 mL of bacterial solution is taken every 12 hours, and its absorbance is detected by a UV spectrophotometer. A total of 5 groups of parallel samples are measured, and each group is repeated 3 times. The pH value of sterile and bacterial culture medium is measured every day for 14 consecutive days.

[0054] Electrochemical testing

[0055] Electrochemical tests were performed in a standard three-electrode electrolytic cell (Reference 1010, Gamry Instruments, USA). The Mg / Q235 CS electrode was used as the working electrode (WE), the saturated calomel electrode (SCE) was used as the reference electrode, and a platinum sheet (10 mm × 10 mm × 1 mm) was used as the counter electrode. An open circuit potential (OCP) test was first performed for 600 seconds until the working electrode reached a stable state. The corrosion state of the sample surface was then characterized by electrochemical impedance spectroscopy (EIS) and potential polarization tests after 7 days. In the EIS, an amplitude of 10 mV and a frequency of 10 -2 Up to 10 5 The EIS data were fitted using Zview2 software (Scribner, Inc.), and the appropriate equivalent circuit (EEC) was selected.

[0056] R was used in sterile culture medium and biological culture medium respectively. s (Q dl R ct ) and R s (Q f (R f (Q dl R ct ))). The potential polarization test was performed in the voltage range of -250 mV to 250 mV (relative to OCP) with a scan rate of 0.125 mV / s.

[0057] In addition, a constant potential test was used to simulate the corrosion and consumption of magnesium under cathodic protection. In the constant potential test, five potential parameters (-1.1V, -1.2V, -1.3V, -1.4V and -1.5V (vs.E ref )) respectively simulate the potential difference between magnesium anode and different cathode materials. In the galvanic test, Q235 CS was used as cathode and magnesium as anode. The test lasted for 7200 seconds and the stable electrochemical corrosion potential (E g ) and current density (i g ).

[0058] Surface characterization

[0059] The morphology of bacterial biofilm and metal surface was characterized by scanning electron microscopy (SEM, FE-SEM, FEIQuanta 250FEG, USA) and laser confocal scanning microscopy (CLAM, Olympus, FV1200, Japan). The biofilm after 3d, 4d, 5d, 6d and 7d of culture was characterized by scanning electron microscopy. Before SEM observation, the biological specimens were fixed with 2.5% glutaraldehyde and then graded dehydrated in ethanol (50, 60, 70, 80, 90, 95 and 100%) for 10 minutes. Then, the dried samples were gold-sprayed by sputtering gold. After 3d, 4d, 5d, 6d and 7d of culture in biological culture medium, the morphology and activity of biofilm were observed by laser confocal microscopy. Before laser confocal microscopy observation, the samples were treated with SYTO9 and propidium iodide fluorescent dye (FilmTracerTM LIVE / DEAD biofilm kit, Thermo Fisher Scientific, USA) in the dark for 20 minutes. The pitting morphology and depth of magnesium were observed using an ultra-depth-of-field microscope (DVM6P, Leica Microsystems, Germany).

[0060] Elemental analysis

[0061] Energy dispersive X-ray fluorescence spectrometer (EDS, FEIQuanta X200, USA) was used to analyze the elements of magnesium sheets after immersion for 7 days; X-ray photoelectron spectroscopy (XPS, Thermo ESCALAB 250Xi, Thermo Electric Company, USA) and X-ray diffraction (XRD, D-MAX 2500 / PC, Rigaku, Japan) were further used to characterize the composition of corrosion products in the presence or absence of bacteria. The XRD scanning range was 5.0°~90.0°, and the XRD spectrum was obtained by Jade 6.5 software; the magnesium ion concentration in the solution was detected by Inductively Coupled Plasma Mass Spectrometry (ICP-MS, NexION1000G, PerkinElmer, USA). The magnesium-containing stock solution (9 mL) soaked in sterile and biological culture medium for 7 days was taken, and 1 mL of dilute nitric acid (GR) was added to neutralize the pH value. Before the test, the solution was filtered with a 0.4μm microfiltration membrane.

[0062] weightlessness

[0063] The weight loss of magnesium sheets was measured by an analytical balance (S220-B produced by Mettler-Toledo, Switzerland). The initial mass of the magnesium sample was weighed immediately after it was taken out of the immersion solution. After the constant potential / galvanic test, the corrosion products on the magnesium surface were ultrasonically cleaned with dilute chromic acid (40g / L CrO3+2g / L AgNO3) at room temperature, then dried and weighed again. The weight loss of the magnesium sheet was the difference between the two weighing values ​​before and after the constant potential test.

[0064] Results and Discussion

[0065] B.altitudinis growth curve

[0066] Microbial preservation can achieve self-regulation, in-situ repair and intelligent protection, providing long-term protection. These benefits are based on the activity of biofilms, which is closely related to the bacterial culture cycle. Different culture times have different effects on the surface under the biofilm, such as surface properties and pH value. Figure 1 a shows the absorbance and planktonic B. altitudinis (N B.altitudinis ) quantity. As can be seen from the figure, the absorbance and N B.altitudinis The linear relationship between them is very good, and the correlation coefficient R 2 is 0.9991.

[0067] Figure 1b shows the growth curve of B.altitudinis. It can be seen that B.altitudinis grew rapidly in the first two days; then B.altitudinis had a 2-day adaptation phase; on the 5th day, the free B.altitudinis continued to grow; then a large number of free bacteria began to aggregate and become adherent bacteria, so on the 7th day, N in the biofilm B.altitudinis At this time, the activity of the adherent bacteria on the biofilm on the magnesium surface may reach the highest level. Next, from the 7th day onwards, the N B.altitudinis The increase continued until the 11th day; however, the activity of B. altitudinis gradually decreased, and in the last 7 days after culture, B. altitudinis entered the decline phase ( Figure 1 b).

[0068] Therefore, the biofilm formed by B.altitudinis after 7 days of cultivation is considered to be the best choice as a smart functionalized bio-coating, which can maintain biological activity for a long time. It should be noted that the test cycle of microbiologically influenced corrosion (MIC) is usually set to 14 days. Because it is necessary to study the impact of the entire bacterial life cycle on the material, including the delayed phase, exponential phase, stable phase and aging phase. In the MIC study, it was also found that the 7-day culture time for bacteria to form a biofilm on the surface of the material is the optimal period for the highest biofilm thickness and activity.

[0069] Figure 1 c shows the change of pH value over time in the presence or absence of B.altitudinis. It can be seen that within the 7th day, the pH value increased rapidly over time and reached greater than 8 on the 7th day; while in the presence of B.altitudinis, the pH value rose slowly from the 7th day to the 11th day. Planktonic bacteria themselves are more likely to secrete large amounts of exogenous polymers (EPS) when they are highly active, thereby affecting the pH value in the culture medium. Once the attached biofilm is formed, the free EPS content in the culture medium is significantly reduced, so the pH value in the culture medium rises slowly. The results also show that B.altitudinis grows well in a weakly alkaline culture environment, explaining why the strain can survive in an alkaline environment caused by the magnesium hydrogenation reaction. After the 11th day, the pH value continued to increase over time, but the growth rate was lower, which is consistent with the Figure 1 This is consistent with the results shown in b, which is due to the gradual decrease in free bacterial activity.

[0070] Bacterial concentration selection

[0071] The smart biofilm coating formed by different bacterial concentrations on the surface of sacrificial anode materials has different effects on the material substrate. Selecting the appropriate bacterial concentration to form the most effective biofilm protection effect is an important prerequisite for this work. Figure 2 a shows the polarization curves of Mg and Q235 CS in biological culture medium, with the bacterial concentration ranging from 10 2 CFU mL -1 Increase to 10 8 CFU mL -1 Table 1 summarizes the corrosion potentials (E corr s) and corrosion current density (I corr s). The cathode hydrogen evolution potential of Q235 CS in LB medium should be around -1.05V ( Figure 2 a) In LB medium, the anodic polarization curves of Q235 CS and Mg do not show obvious passive regions. 3 CFU mL -1 to 10 8 CFU mL -1 When their E corr s and I corr s showed a trend of decreasing first and then increasing. 5 CFU mL -1 When corr The minimum value is 11.53±0.06μAcm -2 The bacterial concentration was 10 7 CFU mL -1 When corr The maximum value is 39.86±0.17μA cm -2 , is the bacterial concentration of 10 5 CFU mL -1 At 10 5 CFU mL -1 The biofilm formed in the bacterial culture medium is like a dense coating attached to the surface of magnesium, which mainly plays a role in inhibiting corrosion. On the other hand, biofilm with a high bacterial concentration will induce severe oxygen concentration corrosion on the surface of the material and accelerate the corrosion rate of the magnesium matrix. Based on this, the protective B.altitudinis concentration of magnesium anode should be 10 5 CFU mL -1 Table 1.E corr ,i corr ,E gi and i givalues ​​obtained from the polarizationcurves of Mg and Q235 CS coupons in sterile and biotic media with variousbacterial numbers(CFU mL -1 )after 7 days of immersion.

[0072]

[0073] Figure 2 The intersection of the cathode polarization curve of Q235 CS (black line) and the anode polarization curve of Mg (colored line) in a (E gi 、i gi ) represents the theoretical galvanic potential and galvanic current density between steel and Mg. Table 1 lists the E gi and i gi The calculated values ​​indicate that if Q235 CS is coupled with magnesium, magnesium can provide cathodic protection for it. 3 CFU mL -1 Increase to 10 8 CFU mL -1 The cathodic protection effect of magnesium on Q235 CS showed a trend of increasing first and then decreasing. 5 CFU mL -1 When E gi (-1.04±0.001V(vs.SCE)) and i gi (97.7±1.25μAcm -2 ) is the smallest, which is consistent with E corr s and I corr The changes in s are consistent.

[0074] Figure 2 b summarizes the Figure 2 E calculated from the polarization curve in a gi s and i gi s. The cathodic polarization curve of Q235 CS in sterile medium has also been added to the graph ( Figure 2 b), which represents bare steel in actual application environment. The cathodic process of Q235 CS is mainly in its E corr and oxygen reduction in most of the cathodic potential range. corr Nearby or near E corrAt cathodic potentials that are not too far away (i.e., in the weak cathodic polarization range), the observed polarization curve deviates from the current platform where oxygen diffusion is limited because the cathodic polarization may still be affected by the anodic dissolution of Q235 CS. In this potential range, the corrosion rate of Q235 CS may still be lower than that at I corr The corrosion rate. Figure 2 As shown in b, when the intersection point (E gi and i gi ) is within this weak cathodic polarization range, it is “inadequately protected”. On the oxygen diffusion plateau, Q235 CS is fully cathodically protected. This region is referred to as “fully protected” in the figure. 5 CFU mL -1 When E gi and i gi This indicates that 10 5 CFUmL -1 The smart functional biofilm on the magnesium anode in the concentrated bacterial solution can provide effective protection for Q235 CS.

[0075] However, if the cathodic polarization is too strong and the potential is less than the hydrogen evolution potential (i.e. -1.05V), the risk of hydrogen embrittlement will increase dramatically. Therefore, this potential region is called "overprotective" in the diagram. 5 CFU mL -1 E gi and i gi In addition, E gi s and i gi s are all within the overprotection range.

[0076] In further experiments, 10 5 CFU mL -1 The B. altitudinis was considered to be the optimal bacterial concentration for forming a functional biofilm on the smart protective magnesium anode.

[0077] Biofilm attachment

[0078] After immersion in biological media for 7 days, the bacterial biofilm attached to the magnesium surface was characterized by scanning electron microscopy (SEM), as shown in Figure 5 shown. Figure 5 a shows the morphology of the magnesium sample cultured in the biological medium. It can be seen that some bacteria with EPS appeared on the surface of the magnesium sample, and some cracks appeared on the surface, which increased the contact area between the magnesium matrix and the culture medium. However, on the third day, the surface was still flat, and there were no obvious corrosion pits on the magnesium surface of the bacteria-containing sample. From the fourth day, the number of bacteria gradually increased. B.altitudinis began to grow and aggregate, forming a bacterial community ( Figure 3b). Thereafter, on days 5 and 6, bacteria multiplied and penetrated into the pores of the matrix ( Figure 3 c), a large number of bacteria aggregated and attached to the magnesium surface ( Figure 3 df). The burr-like crystals MgNH4PO4·6H2O ( Figure 3 c) and inhibited the self-corrosion of magnesium. On the 7th day, a stable and strong biofilm was formed, such as Figure 3 g. Figure 5 h under a high-power scanning electron microscope, it can be further observed that the EPS secreted in the mature biofilm covers the bacteria, making them more firmly bound to the metal surface.

[0079] Accordingly, the results of the measurement of biofilm activity during the 7-day culture period were as follows Figure 4 As shown in the figure, the bacteria remained highly active within 7 days. As the biofilm thickness increased, the coverage of the biofilm also increased from the 3rd day to the 7th day. Figure 6 f shows the Figure 6 The mean fluorescence intensity (MFI) of the biofilm was calculated from the CLSM images of the ae. The MFI value on the third day was 34.8±4.79%, which gradually increased to 78.5±10.9% on the seventh day, which was consistent with the SEM characterization results ( Figure 5 ) is very consistent. The fluorescence efficiency of the Mg surface after 7 days of culture (Figure e) is even 1.8 times and 1.2 times that of the Q235 CS and 304 stainless steel surfaces after 14 days of immersion. The results show that Mg 2+ It can greatly promote the growth of B.altitudinis biofilm in biological culture medium. In addition, from the 5th day of culture, a crystal layer of MgNH4PO4·6H2O can be seen ( Figure 3 c and Figure 4 ce), and the number of crystals increased with the extension of the culture time ( Figure 6 de). The crystalline layer also properly protects the magnesium matrix from corrosion.

[0080] Corrosion resistance test

[0081] Figure 3 a shows the time-dependent changes in the OCP of Mg and Q235 CS samples to investigate their corrosion conditions in sterile and biological media. After 7 days, the OCP value of the Mg sample was approximately 1700 mV (relative to SCE), which shifted negatively compared to Q235 CS (approximately 600 mV (relative to SCE)). There was no significant difference in the OCP values ​​of Mg and Q235 CS samples in the absence and presence of bacteria. Polarization curves of Mg and Q235 CS samples in sterile and bacterial media ( Figure 3b) shows the specific situation of corrosion. It can be seen that the corrosion of Q235 CS specimens in the presence of bacteria is not more serious than that in the absence of bacteria. Table 2 lists their E corr and I corr Value. E of Q235 CS in sterile medium corr The EIS spectra of Mg and Q235 CS coupons in the sterile and biotic media during the 7-day incubation before potentiostatic polarization and galvanic corrosion tests were -0.83±0.004 V (relative to SCE), which is slightly negative than -0.76±0.002 V (relative to SCE) in the biological medium, indicating that Q235 CS has a greater tendency to corrode in the sterile medium.

[0082]

[0083]

[0084] I of Q235 CS in sterile culture medium corr 21.9±0.42μA cm -2 , which is greater than 18.36±0.19μAcm in biological culture medium -2 The results showed that the bacterial concentration was 10 5 CFU mL -1 The biological culture medium has no corrosive effect on the Q235 CS matrix and inhibits the corrosion of Q235 CS to a certain extent. In addition, in the presence of bacteria, the anodic dissolution of magnesium flakes is also inhibited. 5 CFU mL -1 The anodic dissolution concentration in the bacterial culture medium was 11.53 ± 0.06 μA cm -2 , which is lower than 23.34±0.07μAcm in sterile culture medium -2 This indicates that the self-corrosion of magnesium flakes was inhibited in the presence of B. altitudinis.

[0085] In contrast, the E of magnesium samples in sterile culture medium and biological culture medium after 14 days of culture reported by Dong et al. corrThe E values ​​of the magnesium sample after 7 days of culture were -1.56±0.03V (vs.SCE) and -1.47±0.04V (vs.SCE), respectively. corr More negative, indicating that magnesium is less susceptible to corrosion in the biological culture medium after 7 days of culture. corr Only 5.11±0.75μAcm -2 , which is two times lower than that of the magnesium sample after 7 days of culture in biological culture medium. The reason for the suppression of corrosion may be the deposition of the MgNH4PO4·6H2O solid crystalline layer formed by the bacterial biofilm during the 14-day immersion process. However, the MgNH4PO4·6H2O crystal layer is tightly attached and not easy to fall off when the Mg-Fe galvanic couple is connected, making it unsuitable for smart biofilm protection. At the same time, the activity of the biofilm decreased significantly after 14 days, and it could not provide sufficient help for the magnesium anode. The results show that the 7-day culture period of bacterial biofilm on the magnesium surface is suitable, which also verifies that Figure 1 result.

[0086] Figure 6 Nyquist plots of magnesium and Q235 CS specimens exposed to sterile and biological media are shown. The impedance values ​​of the magnesium containing bacteria increased from the first to the fourth day due to the increase in inoculum concentration. Bacterial colonies gradually formed on the magnesium surface ( Figure 3 b). After that, as the bacterial biofilm formed, the impedance of the magnesium tablet containing bacteria gradually increased until it reached a maximum value on the 7th day ( Figure 6 a). The Z value of biological magnesium flakes is about 16kΩcm -2 , an order of magnitude higher than sterile magnesium tablets.

[0087] In addition, the impedance of Q235 CS in sterile culture medium showed little change over 7 days ( Figure 4 d), which means that LB medium has no corrosive effect on Q235 CS within 7 days. The B.altitudinis biofilm formed on the surface of Q235CS sample played a significant protective role and increased the impedance value ( Figure 6 c) This eliminates the concern about adding 10 5 CFU mL -1 The results showed that the B. altitudinis bacterial biofilm significantly inhibited the self-corrosion of the magnesium substrate and had no side effects on the cathode steel. So far, the initial concept of intelligent functional biofilm protection of magnesium anodes in their idle standby state has been realized.

[0088] Anode efficiency test

[0089] Figure 7The results show that the i of magnesium samples in sterile medium and biological medium under -1.5V, -1.4V, -1.3V and -1.2V constant potential corrosion test and Mg-Q235 CS coupled body galvanic corrosion test g s changes. With magnesium samples in sterile medium down to milliampere levels ( Figure 7 a'-e') compared with the magnesium samples in the biological medium. g Keep it at microampere level ( Figure 7 ae). Among them, i measured at a constant potential of -1.5V in biological culture medium g The value is minimum and remains at 111μAcm 2 about( Figure 7 a) In contrast, the magnesium-iron couple in biological culture medium g The value reaches a maximum value of about 650μAcm 2 , which is significantly greater than the value tested at a constant potential of -1.2 V to -1.4 V. In conclusion, the bacterial biofilm plays a key role in maintaining an appropriate galvanic current density, enabling the magnesium anode to provide a long-term stable current output to the cathode material.

[0090] In order to further investigate the protective ability of magnesium anode under smart biofilm, the anodic efficiency of magnesium was calculated based on the results of constant potential / constant current corrosion tests and weight loss. For the anodic polarization when magnesium is coupled to steel, the magnesium dissolution rate I calculated by weight loss measurement Mg The current density is always higher than the constant potential / electrochemical corrosion current I calculated by Faraday's law g This phenomenon is caused by the negative differential effect (NDE) caused by the acceleration of hydrogen evolution when magnesium is polarized by the anode, and the corresponding equation is related to the formula in the reference:

[0091] I g =I Mg -I H ;

[0092] Among them I H is the hydrogen generation rate. This equation clearly shows that the actual dissolved magnesium is enhanced due to the presence of NDE, because the measured I g Below I Mg The anode current efficiency (η) can be calculated by the following formula:

[0093]

[0094] Where ΔW is the weight loss of the magnesium sample before and after the constant potential / electrochemical corrosion test. M is the molar mass, using 24.3 g mol -1 M Mg . N Ais Avogadro's constant, generally 6.02×10 23 . e is the elementary charge, which is 1.6×10 -19 C.

[0095] Figure 8 b shows the anode efficiency measured at different potentials in sterile medium and biological medium. The anode efficiency of the bacteria-containing magnesium sheet is significantly higher than that of the sterile magnesium sheet, especially at -1.2V, -1.3V and Mg-Fe groups. At constant potentials of -1.2V and -1.5V, the efficiency of the sterile magnesium sheet and the biological magnesium sheet is around 50%. This trend is consistent with Figure 8 Mg in a 2+ The trend of dissolved concentration is consistent. In the magnesium-iron coupling group, the anode efficiency of biological magnesium sheet is the highest, reaching 79.8±0.9%. This value is much higher than the protection efficiency of about 50% reported in the literature.

[0096] At constant potentials of -1.3 V and -1.4 V, the anode efficiency of the bio-Mg sheet also remained at a high level, 70.9 ± 2.8% and 73.3 ± 1.8%, respectively. This may be due to the fact that i g The biofilm was inactivated, but it did not fall off from the magnesium surface in large quantities in the constant potential / galvanic corrosion test, and still played a role in protecting the matrix, such as Fig. 9 bd. On the contrary, Fig. 9 As shown in a and e, under the action of too high or too low potential (-1.2V and -1.5V), not only the activity of the biofilm will be reduced, but a large amount of biofilm will also fall off, and it will be unable to continue to protect the substrate during the constant potential test, resulting in low anode efficiency.

[0097] Performance test of magnesium after cathodic protection

[0098] In order to detect the electrochemical performance of anode magnesium after constant potential / galvanic test, Fig.10 The EIS spectra of magnesium anode after constant potential / galvanic test in sterile medium and biological medium are shown. It can be seen that the impedance value of magnesium anode in biological medium is almost twice that in sterile medium ( Fig.10 a and b), which indicates that the smart bacterial biofilm fully protects the anode material, allowing it to maintain high performance after constant potential / galvanic testing. Under the action of a potential difference of -1.2V, the performance of the magnesium anode decreased significantly, and it almost lost its metallic properties. The constant potentials of -1.3V and -1.4V were also unfriendly to the magnesium anode, and its impedance value dropped by an order of magnitude compared with that before the constant potential test ( Figure 6 a). The impedance value of the magnesium anode coupled with Q235 CS is also maintained at 400Ωcm, compared with the impedance values ​​at different constant potentials from -1.2V to -1.5V. 2The results show that the magnesium-iron coupler provides the most suitable potential protection for the Q235 CS cathode without causing excessive damage to the magnesium matrix. In addition, after 7 days of cultivation, the impedance value of the Q235 CS cathode in the biological culture medium was 16 kΩ cm 2 ( Figure 6 c), after galvanic corrosion test, it reached 20kΩcm 2 The higher value ( Fig.10 c), indicating that the magnesium anode provides sufficient protection for the Q235 CS cathode. The magnesium anode provides sufficient protection for the Q235 CS cathode, and the corrosion products on the surface of Q235 CS may cause its impedance value to increase slightly.

[0099] R of magnesium anode and Q235 CS cathode fitted from EIS data f Value and R ct Value comparison see Fig.11 From the 3rd to the 7th day, with the growth of biofilm and the increase of secretions on the magnesium surface, the R f The value showed a clear increasing trend ( Fig.11 a). Day 5, R f The value increased significantly to 742.8±124Ωcm 2 , which is consistent with Figure 3 and Figure 4 Until the 7th day, R f The value is stable at 777.7±72.3Ωcm 2 ( Fig.11 a and Table 2). For the Q235 CS cathode, its R f Values ​​and R of magnesium anode in biological medium f The values ​​show the same trend, such as Fig.11 As shown in b, the R of BioQ235 CS increases with the growth of the biofilm. f The value increased from 1995±44.3Ωcm on the third day 2 Gradually increased to 8130±27.8Ωcm on the 7th day 2 However, after the electrochemical corrosion test, R f The value dropped sharply to 963±107Ωcm 2 ( Fig.11 b and Table 3). In contrast, the R of the magnesium anode after the constant potential / galvanic corrosion test f value( Fig.11 a and Table 3) R before constant potential / galvanic corrosion test f Value (777.7±72.3Ωcm 2 ) is more than an order of magnitude smaller. Fig. 9As shown in a and f, the high potential difference causes the bacterial biofilm to fall off, so the R f The minimum value (9.28±1.32Ωcm 2 ). The inactivated biofilm remained attached to the magnesium surface after being subjected to these potentials, resulting in relatively high R f values ​​and continue to inhibit the self-corrosion of magnesium, so their anode efficiencies are high (79.8±0.9% and 73.34±1.8%, respectively).

[0100] Table 3.Electrochemical parameters from the curve-fitting of EISspectra of Mg and Q235 CS coupons in the sterile and bacterial media during the 14-day incubation after potentiostatic polarization and galvaniccorrosion test.

[0101]

[0102]

[0103] R ct The value reflects the difficulty of electron transfer between the metal surface and the biofilm. ct The value varies in different corrosion situations. Fig.11 c and d show the R of Mg and Q235 CS ct Trends and Fig.11 R shown in a and b f The trend of change is the same, which explains it from another perspective. Fig. 9 b shows the anode efficiency ranking. It is worth mentioning that the R ct The value is still high, 20.13 ± 4.33 kΩ cm 2 ( Fig.11 d and Table 3), compared with 17.53±0.34kΩcm before the galvanic corrosion test 2 The values ​​are similar.

[0104] It can be seen that in this electroplating system, the Q235 CS cathode was well protected, while the smart protective biofilm was not damaged. The slight increase was due to the influence of corrosion products and bacterial secretions on the sample surface. Fig.11It can be clearly seen in c that the R ct The value decreased by more than two orders of magnitude before and after the constant potential corrosion test. ct The value remains at a relatively high 1174±23.3Ωcm 2 , which indicates that the smart biofilm protection performs better under the galvanic potential of Mg-Q235CS.

[0105] Figure 12-16 Shows the surface morphology of the magnesium anode after the constant potential / galvanic corrosion test. Fig.12 ef and Fig.13 ef respectively counted the pitting distribution after galvanic corrosion with the worst protection performance of -1.5V constant potential and the best protection performance. In sterile medium and biological medium, the maximum pitting depth of magnesium anode measured at constant potential of -1.5V was 747.21μm and 428.02μm, respectively. Fig.12 ab and 12c-d. The average pitting depths of magnesium anode in sterile medium and biological medium were 405.99±166.76μm and 192.76±118.06μm, respectively, indicating that the corrosion of magnesium anode in sterile medium was more serious than that in biological medium.

[0106] Likewise, from Fig.12 From the pitting statistics in f, it can be seen that after the -1.5V constant potential test, the pitting depth of the magnesium anode in the sterile culture medium is mainly distributed between 200μm and 700μm, while the pitting depth of the magnesium anode in the biological culture medium is almost between 100μm and 200μm. The pitting depths in the sterile culture medium and the biological culture medium are not much different, which indicates that under the potential difference of -1.5V, the bacterial biofilm of B.altitudinis is difficult to provide sufficient protection for the magnesium anode.

[0107] Fig.13 ab and 13c-d show the maximum pitting morphology of magnesium anode after Q235 CS coupled galvanic test in sterile medium and biological medium. Fig.13 e and f have statistically analyzed the pitting depth. In addition, after galvanic tests in sterile medium and biological medium, the average pitting depths of the magnesium anode plate were 369.42±113.16μm and 154.36±61.64μm, respectively. The pitting depth statistics show that the pitting depth of the magnesium anode in the sterile medium is mainly distributed between 300μm and 500μm. The pitting depth of the magnesium anode in the biological medium is mainly distributed between 100μm and 200μm.

[0108] It is worth noting that after the magnesium-iron galvanic corrosion test, the corrosion of the magnesium anode under biofilm protection was much weaker than that under the -1.5V constant potential test, which indicates that the smart biofilm can provide more effective protection when the magnesium anode is connected to the Q235 CS cathode. This is consistent with the previous conclusion that the magnesium anode can maintain a high anode efficiency (79.8±0.9%) after coupling with the Q235 CS cathode. Similarly, the surface corrosion morphology of the magnesium anode at -1.4V and -1.3V constant potentials with high anode efficiency is not as severe as at -1.5V and -1.2V. The maximum pitting depths at -1.4V and -1.3V are 373.8μm and 379.25μm, respectively, which are significantly smaller than 428.02μm and 456.35μm at -1.5V and -1.2V constant potentials.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a magnesium-based sacrificial anode material protective biofilm, characterized in that: The steps include: The magnesium-based sacrificial anode material is immersed in a Bacillus altitudinis bacterial solution and cultured for a set time to form a biofilm on the surface of the magnesium-based sacrificial anode material.

2. The method for preparing the magnesium-based sacrificial anode material protective biofilm according to claim 1, characterized in that: The concentration of the Bacillus altitudinis bacterial solution is 10 4 -10 6 CFU / mL.

3. The method for preparing the magnesium-based sacrificial anode material protective biofilm according to claim 2, characterized in that: The concentration of the Bacillus altitudinis bacterial solution is 10 5 CFU / mL.

4. The method for preparing the magnesium-based sacrificial anode material protective biofilm according to claim 1, characterized in that: The magnesium-based sacrificial anode material is pure magnesium, Mg-6Al-3Zn, Mg-5Al-0.5Zn, AZ91D, Mg-0.5Mn, Mg-6Al-3Zn-0.2Mn, Mg-5Al-0.5Zn-0.5Mn-0.5RE, Mg-6Al-3Zn-0.5RE or Mg-7Al-1Zn-0.2Ca-0.2Sr.

5. The method for preparing the magnesium-based sacrificial anode material protective biofilm according to claim 1, characterized in that: The magnesium-based sacrificial anode material is cultured in the Bacillus altitudinis bacterial solution for 5-10 days.

6. The method for preparing the magnesium-based sacrificial anode material protective biofilm according to claim 5, characterized in that: The magnesium-based sacrificial anode material is cultured in the Bacillus altitudinis bacterial solution for 6-8 days.

7. The method for preparing the magnesium-based sacrificial anode material protective biofilm according to claim 6, characterized in that: The magnesium-based sacrificial anode material is cultured in the Bacillus altitudinis bacterial solution for 7 days.

8. The method for preparing the magnesium-based sacrificial anode material protective biofilm according to claim 1, characterized in that: The temperature at which the magnesium-based sacrificial anode material is cultured in the Bacillus altitudinis bacterial solution is 28-37°C.

9. A magnesium-based sacrificial anode material for protecting biofilm, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.

10. A method for protecting magnesium-based sacrificial anode materials by using the magnesium-based sacrificial anode material protection biofilm according to claim 9, characterized in that: The steps include: When the cathode material does not need protection, there is no current between the cathode material and the magnesium-based sacrificial anode material. At this time, the biofilm on the surface of the magnesium-based sacrificial anode material protects the magnesium-based sacrificial anode material and inhibits its self-corrosion. When the cathode material needs protection, the current formed between the cathode material and the magnesium-based sacrificial anode material inactivates the biofilm, and the protection of the cathode material by the magnesium-based sacrificial anode material is initiated.